Enhancing MSME Credit Access in Emerging Markets through Open Banking: Evidence from Cash-Flow Based Lending - Adelia Riana Dewi; Dia Ragasari (Asosiasi Dosen Muda Indonesia, 2025)
This study investigates the impact of Open Banking adoption on micro, small, and medium enterprise (MSME) credit access in emerging economies, with a specific focus on cash-flow based lending enabled through account aggregation APIs. Utilizing panel data of 150 MSMEs that applied for bank or fintech credit between 2022 and 2024, we employ fixed-effects regression to examine how the API Adoption Index and Cash-Flow Completeness Score influence approval rate, time-to-decision (“time-to-yes”), and non-performing loan (NPL) ratios. Results indicate that a 10 % increase in the API Adoption Index is associated with a 4.2 % rise in approval rate (p < 0.01), a 35 % reduction in time-to-yes, and a 1.8 percentage point reduction in NPL. These findings fill a critical gap in literature by providing empirical evidence specific to emerging-market MSMEs and highlight policy implications for regulators and financial institutions aiming to boost inclusive lending through data sharing frameworks.